PARASOCIAL INTERACTION PHENOMENON ON SELEBGRAM'S INSTATORY PAGE (International Conference on Social and Islamic Studies, 2022)
Digital interactions with social media consistently result in new releases that feature elaborate features. In social media, interactions between celebrities on Instagram or in other celebrity-related contexts provide a new way for followers and the celebrity in question to interact. In 2022, Indonesia will have a large proportion of social media influencers in every country. According to this data, the percentage of influencers will rise to more than 40% by the year 2020. One influencer account that currently has a sizable following is @dindarahmawatis, who has experience creating content about the lives of other people, particularly children. The interaction between the owner of the account @dindarahmawatis and their followers has been growing steadily, and this is in line with the theory of parasitic interaction put forward by Auter and Palmgreen in the year 2021. . The purpose of this study is to determine the relationship between social interaction patterns and the theme of missing children on the Instagram account of @dindarahmawatis. The method used is deskriptif kualitatif, with the initial data being text from the Instastory account of @dindarahmawatis and data being pulled every second from wawancara results with account holders. The findings of the study indicate that the owner of the account @dindarahmawatis engaged in parasocial interactions that primarily focused on three factors: task attraction, romantic attraction, and identity attraction. A personal communication strategy is used, along with positive feedback to followers, courteous language, and a humble demeanor, all of which are backed by the outward look of Muslim women who are used as role models for followers. These factors dominate the method taken. Further research that explicitly investigates interactions on new media pages can use this study as a source of inspiration. Keywords : Interpersonal communication, social media, and Parasocial Interaction